X-ray computed tomography study of kink bands in unidirectional composites. (15th January 2017) - Wang, Ying; Burnett, Timothy L.; Chai, Yuan; Soutis, Costas; Hogg, Paul J.; Withers, Philip J.
Abstract: An experimental study on the axial compressive failure of cylindrical unidirectional (UD) carbon fibre-epoxy rods has been performed to better understand kink bands and the relevant damage mechanisms in three dimensions (3D). Post-mortem X-ray micro-computed tomography (micro-CT) imaging has shown that fibre kink bands predominantly all lie within the same plane in a cylindrical rod sample uniaxially compressed without lateral constraint. Kink bands at different stages of development are contained in the damage volume and the geometric parameters of fully developed kink bands are consistent through the damage zone, with a kink-band width ω  ≈ 20–320 μm, kink-band angle β  ≈ 11–40° and fibre rotation angle Φ ( φ  +  φo ) ≈ 18–52°. Fibre failure, longitudinal splitting and matrix micro-cracks within the fibre kink zone are identified by scanning electron microscopy (SEM) and X-ray micro-CT observations. The smallest radius of curvature that corresponds to maximum amount of bending of the unbroken buckled fibres was ∼280 μm (40 fibre diameters). Kink-band boundary planes and longitudinal splitting have been extracted and visualised in 3D for the first time.